Clear intelligence is personal among students of Wasit University - Hamid Al-Atabi, Abdullah Majeed (International Journal of Psychosocial Rehabilitation, 2020)
University education is one of the most important educational stages, as it represents the top of the educational pyramid and aims to prepare individuals in an orderly and life-oriented manner, so it receives a lot of care and attention in most developed and developing countries alike, for the important role it plays in human, social and economic development and what provides of an amazing workforce and community leadership, which requires preparation and attention to the human element psychologically and socially so that it can respond to the givens of the age and society. Since the current research aims to describe the interpersonal intelligence of its undergraduate students, so the researcher has adopted the descriptive approach that seeks to determine the current situation of the phenomenon studied. In order to achieve the objectives of the current research and to measure the research variable, the researcher built a personal evidence scale, whereby a number of conclusions, recommendations and proposals were reached, the details of which will be mentioned later.